Correlation of Rapid Cell Death with Metabolic Changes in Fungus-Infected, Cultured Parsley Cells. - Naton, B. (1996)
To study in detail the hypersensitive reaction, one of the major defense responses of plants against microbial infection, we used a model system of reduced complexity with cultured parsley (Petroselinum crispum) cells infected with the phytopathogenic fungus Phytophthora infestans. Experimental conditions were established to maintain maximal viability of the cultured cells during co-cultivation with fungal germlings, and a large proportion of the infected parsley cells responded to fungal infection with rapid cell death, thereby exhibiting major features of the hypersensitive reaction in whole-plant-pathogen interactions. Rapid cell death clearly correlated with termination of further growth and development of the fungal pathogen. Thus, the system fulfilled important prerequisites for investigating cell-death-related metabolic changes in individual infected cells. Using cytochemical methods, we monitored the increase of mitochondrial activity in single infected cells and the intracellular accumulation of reactive oxygen species prior to the occurrence of rapid cell death. We obtained strong correlative evidence for the involvement of these intracellularly accumulating reactive oxygen species in membrane damage and in the resulting abrupt collapse of the cell.